2018
DOI: 10.1634/theoncologist.2018-0382
|View full text |Cite|
|
Sign up to set email alerts
|

High-Grade Gastrointestinal Neuroendocrine Carcinoma Management and Outcomes: A National Cancer Database Study

Abstract: Background High‐grade neuroendocrine carcinomas are rare in the gastrointestinal tract. However, treatment patterns and outcomes have not been well described. Subjects, Materials, and Methods The National Cancer Database was analyzed. The primary objective was to describe the clinical outcomes and identify prognostic factors. Univariate and multivariate analyses were done to identify factors associated with patient outcome. Results A total of 1,861 patients were identified between 2004 and 2013. The mean age w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
60
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(65 citation statements)
references
References 30 publications
5
60
0
Order By: Relevance
“…1,2 NECs are highly aggressive neoplasms that often present at an advanced stage; therefore, chemotherapy is often the primary therapeutic approach. 3 The prognosis of gastric NEC remains poor despite current treatment strategies, including platinum-containing regimens, which have been extrapolated from the management guidelines for small-cell lung cancer, [4][5][6] and there is an urgent need to identify molecular targets that are effective in patients with this aggressive neoplasm.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 NECs are highly aggressive neoplasms that often present at an advanced stage; therefore, chemotherapy is often the primary therapeutic approach. 3 The prognosis of gastric NEC remains poor despite current treatment strategies, including platinum-containing regimens, which have been extrapolated from the management guidelines for small-cell lung cancer, [4][5][6] and there is an urgent need to identify molecular targets that are effective in patients with this aggressive neoplasm.…”
Section: Introductionmentioning
confidence: 99%
“…Thereafter, several small retrospective studies have reported ORRs for this regimen that widely range from 17 to 63% [70][71][72][73][74]. More recent large tumor registries have confirmed the efficacy of CDDP-VP-16 in this setting, although ORRs (28-48%) are generally lower than those reported for SCLC [69,[75][76][77][78].…”
Section: First-line Chemotherapymentioning
confidence: 99%
“…There has been a gradual growth in the incidence of NETs in recent years but no signi cant change in the survival of patients with high-grade NET [16,21]. This situation may re ect a lack of awareness in the treatment.…”
Section: Discussionmentioning
confidence: 99%
“…This situation may re ect a lack of awareness in the treatment. Given the biological similarities, the main treatment of NET was extrapolated from the experience in small-cell lung cancer (SCLC) currently [14,16,22]. Neoadjuvant therapy in SCLC has been proved effective in some studies [23][24][25].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation